The effects on customer satisfaction and customer loyalty by integrating marketing communication and after sale service into the traditional marketing mix model of Umrah travel services in Malaysia - Othman, Bestoon Abdulmaged; Harun, Amran; De Almeida, Nuno Marques; Sadq, Zana Majed (Emerald Publishing Limited, 2021)
Purpose – With growing mobility in a globalized world and an estimate of more than 300 million people going on religious pilgrimages every year, various researchers have been focusing on pilgrimage-driven travel services. In this context and within the Islamic religious tradition, the “Umrah” is used as a case study in this paper. In addition, this study also investigated the effects of Umrah SMM (promotion, place, people, product, price, process, physical evidence, marketing communication and after sale service) on customer satisfaction and loyalty toward Umrah travel agents in “Malaysia.” Design/methodology/approach – Convenience sampling technique at four international airports in “Malaysia” was used to obtain data from Umrah travelers who had used Umrah services at least once. A total of 384 usable questionnaires were collected from this study and the data were analyzed using the partial least square. Findings – The result indicated that the marketing mix has a significant positive effect on customer loyalty through customer satisfaction both directly and indirectly. This study will be of interest to the Umrah travel industry, for Malaysia and all the other countries, in understanding how marketing mix strategies are essential in maintaining a long-term relationship with customers. Originality/value – The literature on Umrah travel services revealed that the traditional service marketing mix (SMM) of 7P’s is inadequate. The purpose of this paper is to address this gap and examine an innovative service marketing mix strategy for “Umrah Service” including marketing communication and after sales service. It investigates the effects of enhanced Umrah SMM on customer satisfaction and loyalty towards Umrah travel agents in “Malaysia”.